Embedding Local Wisdom in Sustainable Mangrove Ecotourism: A Tri Hita Karana Perspective (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2026)
Tourism development has generated economic benefits while increasing environmental degradation, particularly in sensitive coastal ecosystems such as mangrove forests. Sustainable tourism therefore requires management approaches that integrate environmental conservation, community participation, and local cultural values. This study examined the implementation of sustainable tourism based on the Tri Hita Karana philosophy at a Mangrove Ecotourism in Bali. A qualitative case study approach was employed using purposive sampling. Data were collected through semi-structured interviews with ecotourism managers, tour guides, fishermen, and visitors, supported by participant observation and document analysis. The data were analyzed using thematic analysis. The findings showed that the three dimensions of Tri Hita Karana were embedded in ecotourism management practices. The Parahyangan dimension was reflected in religious rituals and spiritual activities supporting environmental conservation. The Pawongan dimension promoted community empowerment through employment, stakeholder collaboration, and environmental education. The Palemahan dimension emphasized mangrove conservation through waste management, visitor control, ecosystem restoration, and biodiversity protection. The study demonstrated that Tri Hita Karana functioned as an operational governance framework that integrated spiritual, social, and ecological values to support sustainable mangrove ecotourism management.